2021
DOI: 10.1016/j.isci.2020.101909
|View full text |Cite
|
Sign up to set email alerts
|

Single synapse glutamate imaging reveals multiple levels of release mode regulation in mammalian synapses

Abstract: Summary Mammalian central synapses exhibit vast heterogeneity in signaling strength. To understand the extent of this diversity, how it is achieved, and its functional implications, characterization of a large number of individual synapses is required. Using glutamate imaging, we characterized the evoked release probability and spontaneous release frequency of over 24,000 individual synapses. We found striking variability and no correlation between action potential-evoked and spontaneous synaptic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 72 publications
(102 reference statements)
5
21
0
Order By: Relevance
“…iGluSnFR accurately reported glutamate release events as evidenced by the detection of synaptic failures in our data (Figure 2A-B), with a high signal to noise ratio (Figure 2C). These data are consistent with other studies using neuronal cultures (Farsi et al, 2021; Tagliatti et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…iGluSnFR accurately reported glutamate release events as evidenced by the detection of synaptic failures in our data (Figure 2A-B), with a high signal to noise ratio (Figure 2C). These data are consistent with other studies using neuronal cultures (Farsi et al, 2021; Tagliatti et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…These results expand upon earlier work that validated iGluSnFR at single synapses (Farsi et al, 2021; Tagliatti et al, 2020), and demonstrates that iGluSnFR detects quantal release for both evoked and spontaneous release. In these experiments we also observed the detection of these different modes of release can be modulated by established parameters, such as Ca 2+ and hypertonicity.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Dürst and colleagues used fast spiral scanning of iGluSnFr to localize points of presynaptic glutamate release (vesicle fusion) within single boutons in slice cultures (Dürst et al, 2019). Farsi and colleagues demonstrated that single quantal vesicular release can be detected by iGluSnFr in hippocampal boutons in neuronal culture (Farsi et al, 2021). In combination with other tools such as cell type-specific optogenetic or chemogenetic actuators, these sensors allow us to gain an understanding of circuit-specific mechanisms with unprecedented spatial resolution, which is difficult to achieve with microdialysis or FSCV.…”
Section: Mesoscopic and Microscopic View Of Neurotransmitter And Neuromodulator Releasementioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 15 While much work has been done to develop open-source image analysis software for in vivo calcium imaging (Cantu et al, 2020;Giovannucci et al, 2019;Tegtmeier et al, 2018), the inherent differences between intracellular expressed calcium indicators and synaptic and membrane targeted transmitter sensors may limit their translatability. Detecting and quantifying neurochemical release at the level of individual synapses have been explored (Dürst et al, 2019;Farsi et al, 2021), and perhaps recent advances in synapse detection algorithms for fluorescent images may further improve the accessibility and accurate quantification of synaptic release analysis using GEIs (Feng et al, 2012;Kulikov et al, 2019;Wang et al, 2019). An open-source software suite (pMAT) for analysis of fiber photometry data has been recently developed, allowing for implementation of a standardized data analysis pipeline across groups (Bruno et al, 2021).…”
Section: Challenges In Image Analysismentioning
confidence: 99%